1999
DOI: 10.1108/02644409910266403
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of trusses using genetic algorithms for discrete and continuous variables

Abstract: This paper demonstrates the use of genetic algorithms (GAs) for size optimization of trusses. The concept of rebirthing is shown to be considerably effective for problems involving continuous design variables. Some benchmark examples are studied involving 4‐bar, 10‐bar, 64‐bar, 200‐bar and 940‐bar two‐dimensional trusses. Both continuous and discrete variables are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 9 publications
0
40
0
Order By: Relevance
“…Table 3 shows the best and worst results of 20 independent runs for the different PSO approaches. Other published results found for the same problem using different optimization approaches including gradient based algorithms both unconstrained (Schimit & Miura, 1976), and constrained (Gellatly & Berke, 1971;Dobbs & Nelson, 1976;Rizzi, 1976;Haug & Arora, 1979;Haftka & Gurdal, 1992;Memari & Fuladgar, 1994), structural approximation algorithms (Schimit & Farshi, 1974), convex programming (Adeli & Kamal, 1991, Schmit & Fleury, 1980, non-linear goal programming (El-Sayed & Jang, 1994), and genetic algorithms (Ghasemi et al, 1997;Galante, 1992) are also shown in Tables 3 and 4. Table 4.…”
Section: Example 1 -The 10-bar Trussmentioning
confidence: 97%
“…Table 3 shows the best and worst results of 20 independent runs for the different PSO approaches. Other published results found for the same problem using different optimization approaches including gradient based algorithms both unconstrained (Schimit & Miura, 1976), and constrained (Gellatly & Berke, 1971;Dobbs & Nelson, 1976;Rizzi, 1976;Haug & Arora, 1979;Haftka & Gurdal, 1992;Memari & Fuladgar, 1994), structural approximation algorithms (Schimit & Farshi, 1974), convex programming (Adeli & Kamal, 1991, Schmit & Fleury, 1980, non-linear goal programming (El-Sayed & Jang, 1994), and genetic algorithms (Ghasemi et al, 1997;Galante, 1992) are also shown in Tables 3 and 4. Table 4.…”
Section: Example 1 -The 10-bar Trussmentioning
confidence: 97%
“…It is based on natural selection and survival of the fittest and has been successfully applied to the optimum design of structures [12,13]. In the application presented in this paper, the components of en and ev should be determined firstly, and also the matrix En and Ev should be calculated accordingly.…”
Section: Linear Displacement Controlmentioning
confidence: 99%
“…Another stochastic search technique named genetic algorithms (GA) is employed to deal with the optimization problem in this article. It is s based on natural selection and survival of the fittest and has been successfully applied to the optimum design of structures [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…For the discrete case the values of the cross-sectional areas (in 2 ) are chosen from the set S with 42 options: [40], a total of 64 strings are available. In this way, the first 22 values of the set S (from 1.62 to 4.59) are listed twice (1.62, 1.62, 1.80, 1.80, etc.).…”
Section: Test-problem 5-the Ten-bar Trussmentioning
confidence: 99%